High hiding power titanium dioxide and method for preparing the same

CN120646902BActive Publication Date: 2026-10-30JIANGSU TOP FINE NEW RAW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510986216.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2026-10-30
Estimated Expiration
2045-07-17

AI Technical Summary

Technical Problem

该方案制得的晶种在400-1100nm范围内的粒子为60%以上,晶种的粒径较大,且晶种的粒径分布太宽,制得钛白粉的遮盖力有待提升

Benefits of technology

(1)碱液预热再加入加热后的钛液中,避免了钛液局部反应温度的降低,确保晶种的活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120646902B_ABST
    Figure CN120646902B_ABST
Patent Text Reader

Abstract

The application discloses high-hiding-power titanium white and a preparation method thereof, and comprises the following steps: taking a titanyl sulfate solution with a concentration of 80-100 g / L, an F value of 1.95-2.05 and Fe / TiO2 of 0.2-0.28, heating the titanyl sulfate solution to 40-55 DEG C, preheating alkali liquor to 30-40 DEG C, adding the preheated alkali liquor into the heated titanyl sulfate solution, adding the preheated alkali liquor for 30-40 minutes, controlling the final pH value to 3.0-4.0, increasing the temperature to 60 DEG C for aging, aging for 10-30 minutes, cooling to below 25 DEG C, and filtering to obtain crystal seeds with uniform particle size; preparing wet-ground titanium white slurry; coating, aging, washing, drying and steam-powdering the wet-ground titanium white slurry, and the high-hiding-power titanium white is obtained. The hiding power of the titanium white is greater than 93% through the shape and size of titanium white particles and coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium dioxide, and more particularly to a high hiding power titanium dioxide and its preparation method. Background Technology

[0002] The most important role of titanium dioxide pigment in industry lies in its opaque property when dispersed in a medium, which enables it to achieve a masking effect. The hiding power of a pigment depends not only on its crystal structure, refractive index, and light scattering ability, but also on its light absorption ability. However, like other white pigments, titanium dioxide has a very low light absorption ability. While light absorption does affect hiding power, its impact is not as significant as scattering ability; therefore, its hiding power is primarily influenced by scattering.

[0003] The different shapes and sizes of titanium dioxide particles result in vastly different degrees of light scattering, which is a key factor affecting the hiding power of titanium dioxide.

[0004] Chinese patent CN103880070B discloses a method for producing titanium dioxide particles. This method utilizes an existing sulfuric acid process titanium dioxide production line. By adjusting and improving process parameters and operating methods, including titanium liquid parameters, seed preparation, atmospheric pressure hydrolysis, salt treatment, calcination, and post-treatment, and by making corresponding adjustments to detection and control, a method yields titanium dioxide with over 60% particles in the 400-1100 nm range, all of which are fully rutile. The titanium dioxide particles produced by this method exhibit excellent reflectivity to the near-infrared portion of sunlight, resulting in good cooling and energy-saving effects in coatings and plastic products made from them. However, the seed crystals obtained by this method have over 60% particles in the 400-1100 nm range, resulting in relatively large particle sizes and a wide particle size distribution. Therefore, the hiding power of the produced titanium dioxide needs improvement. Summary of the Invention

[0005] The present invention aims to provide a high-opacity titanium dioxide and its preparation method. By the interaction of the shape, size and coating of titanium dioxide particles, the degree of light scattering of titanium dioxide particles is improved, thereby improving the opacity of titanium dioxide.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing high-opacity titanium dioxide includes the following steps: S1. Take a titanium oxysulfate solution with a concentration of 80-200 g / L, an F value of 1.95-2.05, and an Fe / TiO2 ratio of 0.2-0.28. Heat the titanium oxysulfate solution to 40-55℃, preheat the alkali solution to 30-40℃, add the preheated alkali solution to the heated titanium oxysulfate solution, and add the preheated alkali solution for 30-40 minutes. Control the final pH value to 3.0-4.0, then raise the temperature to 60℃ for aging for 10-30 minutes, and then cool to below 25℃ to obtain a seed crystal solution. S2. Filter the seed solution obtained in S1 to remove seed crystals with a particle size greater than 0.35 μm; S3. Filter the seed solution after S2 again to remove seed crystals with a particle size of less than 0.16μm, and obtain the filtered seed solution. S4. Add the filtered seed solution prepared in S3 to the titanium liquid, and then perform hydrolysis, first washing, bleaching, second washing, salt treatment, calcination, preparation of rutile titanium dioxide powder, roller milling, and wet milling to obtain wet-milled titanium dioxide slurry. S5. Coat, mature, wash, dry, and air-powder the wet-milled titanium dioxide slurry from S4 to obtain the final product.

[0007] In S2, remove seed crystals with a particle size greater than 0.35 μm and remove coarse-sized seed crystals.

[0008] In step S3, seed crystals with a particle size smaller than 0.16 μm are removed, and fine seed crystals are removed to obtain a filtered seed crystal solution.

[0009] The F-value of a titanium oxysulfate solution, also known as the acidity coefficient, is the ratio of the effective acid concentration to the total titanium mass concentration in the titanium solution. Its calculation formula is: The effective acid is the sum of the mass concentrations of the acid bound to titanium and the free acid. Fe / TiO2 is the mass of iron divided by the mass of TiO2, ranging from 0.2 to 0.28.

[0010] This invention controls the particle size of hydrolyzed seed crystals and removes large and fine particles through a two-stage filtration method to obtain seed crystals with a particle size of 0.16-0.35 μm. Seed crystals with a suitable particle size are beneficial for subsequent water washing. If the particle size distribution is uneven, there will be more fine and coarse particles, which tend to aggregate firmly, resulting in high viscosity of metatitanic acid and a long water washing time. Seed crystals with a suitable particle size are provided for titanium liquid hydrolysis. The prepared hydrolyzed metatitanic acid has a moderate particle size and narrow distribution, ultimately producing titanium dioxide with high hiding power, as detailed below: (1) Under the same conditions, when the particle size of titanium dioxide is 160-350nm, that is, when the particle size is about 0.4-0.5 times the wavelength of visible light, it has a strong ability to scatter light, which will directly affect the hiding power of the coating in application.

[0011] High scattering power, and consequently high hiding power, can only be obtained when the particle size is controlled within 0.4 to 0.5 times the wavelength range of visible light (0.4-0.7 μm), i.e., between 0.16 and 0.35 μm. The main factors affecting the hiding power of titanium dioxide pigments after film formation are particle size and dispersibility. If the titanium dioxide particle size is very fine, with many particles smaller than 0.16 μm, the hiding power of the titanium dioxide will be low. Similarly, if the titanium dioxide particle size is very coarse, with many particles larger than 0.35 μm, the hiding power of the titanium dioxide will also be low.

[0012] (2) The fine-particle seed crystals were removed, and the overburning of excessively fine particles was avoided during the calcination of metatitanic acid, thus avoiding the influence of sintered particles on the covering force.

[0013] To ensure the preparation of seed solutions with a particle size range of 0.16-0.35 μm, this application employs the following methods to achieve the desired interaction: S1: The concentration of the titanium oxysulfate solution is controlled at 80-100 g / L. If the concentration of the titanium solution is too low, there is a risk of premature hydrolysis. If the concentration of the titanium solution is too high, according to the reaction principle, the reactant TiO2 will have more opportunities to collide with the alkali, resulting in extremely fine seed crystals.

[0014] An F value of 1.95-2.05 indicates low acidity and a risk of premature hydrolysis in the titanium solution. An F value that is too high indicates high acidity; in the same solution, H... + High ion concentration, H + More opportunities for collision with alkali will result in more formation of extremely fine crystal seeds.

[0015] The titanium liquid is heated to 40-50℃. If the reaction temperature is too low, the reaction rate is too slow, and too many seed crystals with uneven particle sizes are produced. Seed crystal formation involves both nucleus formation and growth, which occur simultaneously and compete with each other. When the reaction rate is slow, the nucleation rate is slow, and the growth time is long. The particles that nucleate first are much larger than the seed crystals that nucleate later due to the long growth time, and the overly coarse seed crystals will indirectly affect the covering power. If the reaction temperature is too high, the reaction rate is too fast, and too many extremely fine seed crystals are produced. Too many extremely fine seed crystals not only affect the yield of seed crystals with suitable particle sizes but also affect subsequent filtration.

[0016] Preheat the alkali to 30-40℃ to avoid lowering the temperature of the titanium oxysulfate solution upon addition, which would cause a localized drop in the solution's temperature and affect the rate of crystal nucleation. If the alkali solution is not preheated and is added directly to the titanium solution while it is still cold, the local temperature at the point of addition will decrease, resulting in low-activity seed crystals formed at this localized low temperature.

[0017] The alkali should be added within 30-40 minutes. If the alkali addition time is too short, the reaction between titanium oxysulfate and the alkaline solution will be too vigorous, resulting in extremely fine seed crystals. If the alkali addition time is too long, the reaction rate between the titanium oxysulfate solution and the alkaline solution will be slow, which may lead to premature hydrolysis of the titanium solution. Preferably, the alkali addition time is 35-40 minutes.

[0018] S4 titanium solution is a colloidal solution containing liquid Ti and a large amount of impurities such as iron. The hydrolysis product is a suspension containing solid Ti and a large amount of impurities such as iron. The hydrolyzed hydrated titanium dioxide contains sulfuric acid and ions such as iron, aluminum, manganese, copper, nickel, vanadium, and lead. These ions will generate corresponding oxides after calcination, exhibiting various colors and thus contaminating the product to varying degrees. Therefore, it is necessary to wash them with water to remove them. Hydrated titanium dioxide is insoluble in water, while sulfuric acid and ions such as iron, aluminum, manganese, copper, nickel, vanadium, and lead are soluble in water. This is a prerequisite for water washing. The concentration difference between the washing water and the impurity ions in the hydrated titanium dioxide is used to remove the impurities. After the first wash, the hydrated titanium dioxide still contains trivalent iron, which exists in the form of Fe(OH)3. This needs to be bleached to convert the solid Fe(OH)3 into soluble Fe2(SO4)3, followed by a second wash for further impurity removal.

[0019] According to an embodiment of the present invention, the present invention can be further optimized. The optimized technical solution is as follows: In S1, the alkaline solution is added to the titanium oxysulfate solution, and the pH reaches 2.0 in 18-20 minutes.

[0020] In one preferred embodiment, in S1, an alkaline solution is added to a titanium oxysulfate solution, and the time for the pH to reach 2.5 from 2.0 is 5-8 minutes, the time for the pH to reach 3.0 from 2.5 is 3-6 minutes, the time for the pH to reach 3.5 from 3.0 is 2-5 minutes, and the time for the pH to reach 4.0 from 3.5 is 1-3 minutes.

[0021] Supersaturation significantly affects the formation of crystal nuclei and the rate of crystal growth, which in turn influences the particle size and distribution of the hydrolysis products. In the initial stage of the reaction, the titanium concentration in the titanium oxysulfate solution is high. To ensure saturation, a large amount of alkali is required, necessitating a rapid alkali addition flow rate. However, this rate cannot be excessive; otherwise, excessively rapid alkali addition will result in locally high alkali concentrations. Given the limited concentrations of TiO2 and acid in the titanium solution, this will promote the reaction of alkali with iron in the titanium oxysulfate solution to form ferrous precipitate, which is a poor seed crystal. In the later stage of the reaction, the titanium concentration in the titanium oxysulfate solution is low. To avoid excessive saturation, a smaller amount of alkali is required, necessitating a slow alkali addition flow rate.

[0022] In S1, the alkaline solution is added to the titanium oxysulfate solution via an axial flow pump.

[0023] In one preferred embodiment, in step S1, an alkaline solution is added to a titanium oxysulfate solution, and the final pH value is controlled to be 3.5-4.0.

[0024] The endpoint pH value is controlled between 3.5 and 4.0. If the pH value is too low, the amount of seed crystals prepared will be small, and if the pH value is too high, it will easily cause early hydrolysis of the seed titanium liquid.

[0025] In one preferred embodiment, the concentration of the alkaline solution in S1 is 60-80 g / L. The alkaline solution includes one or two of LiOH, NaOH, and KOH. The concentration of the alkali solution is 60-80 g / L. If the concentration of the alkali is too low, it will be added to the titanium solution to reduce the concentration of the titanium solution and promote the hydrolysis of the titanium solution and seed crystals during the reaction. If the concentration of the alkali is too high, the reaction between the alkali solution and the titanium solution will be too violent, which will cause the local temperature of the reactants to be too high and the local TiO2 will undergo premature hydrolysis.

[0026] In one preferred embodiment, in S2, a Buchner funnel with filter cloth is used to filter out coarse seed crystals.

[0027] The concentration of titanium dioxide, the iron-to-titanium ratio, the F value, the hydrolysis temperature, and the hydrolysis time all affect the particle size and particle size distribution of hydrolyzed metatitanic acid. The particle size distribution of hydrolyzed metatitanic acid cannot be absolutely uniform; excessively fine particles will inevitably exist. Further filtration is then used to remove coarse and fine seed crystals.

[0028] In one preferred embodiment, in S3, a ceramic membrane filter is used to remove the seed crystals of fine particles, and the filtration is performed by a water circulation pump.

[0029] In one preferred embodiment, the coating process in step S5 specifically includes the following steps: preparing a wet-milled titanium dioxide slurry to a concentration of 300-500 g / L, heating it to 45-60°C, adding sodium silicate with a mass concentration of 4-5% over 20-40 minutes, adding an acidifying agent with a mass concentration of 5-10% until the pH of the slurry reaches 5.0-6.5 over 40-60 minutes, maturing for 10-20 minutes, adding an aluminum sulfate solution with a mass concentration of 2-10%, and then adding a dilute alkali solution with a mass concentration of 5-10% to control the pH of the slurry to 8-10 over 30-40 minutes.

[0030] The sodium silicate addition is 4-5%. Insufficient sodium silicate affects the dispersibility of titanium dioxide, thus impacting its hiding power; excessive sodium silicate affects its performance. The addition time is 20-40 minutes; too short or too long a time is detrimental to the coating of hydrated silica onto the surface of the titanium dioxide particles. Add 5-10% dilute acid as an acidifier; the acidifier in S5 can be either hydrochloric acid or sulfuric acid. Adjust the pH to 5.0-6.5; too high a pH prevents complete formation of silicic acid from sodium silicate, while too low a pH easily dissolves the formed silicic acid sol. Mature for 10-20 minutes. Add 2-3% aluminum sulfate solution, followed by 5-10% dilute alkali solution, controlling the slurry pH to 8-10. This allows aluminum hydroxide to coat the TiO2 particles.

[0031] This invention features a low coating temperature and a porous silicon coating method, resulting in exceptionally high opacity. In contrast, Chinese Patent CN103880070B uses a high coating temperature and a dense silicon coating method, but lacks exceptional opacity.

[0032] When dilute sulfuric acid is added to S5, sodium silicate forms silica gel.

[0033] Na2SiO3+ H2SO4= Na2SO4+ SiO2.nH2O Aluminum sulfate solution reacts with alkaline solution to form aluminum hydroxide.

[0034] Al2(SO4)3+6 NaOH = 3Na2SO4+2Al(OH)3 In one preferred embodiment, the aging time after adding the dilute alkali solution in S5 is 10-15 minutes.

[0035] Preferably, the pH value is adjusted to 3.5-4.0 after filtration in step S3; a dilute acid solution is added to step S3 to adjust the pH value. Adding dilute acid to control the pH value of the seed crystal solution is to ensure the activity of the seed crystals.

[0036] The present invention also discloses a high-coverage titanium dioxide prepared according to the preparation method described above.

[0037] Compared with the prior art, the beneficial effects of the present invention are: (1) The alkaline solution is preheated and then added to the heated titanium solution to avoid the local reaction temperature of the titanium solution being reduced, thus ensuring the activity of the seed crystals.

[0038] (2) Controlling the pH value at the end of seed preparation can ensure the activity of the prepared seed crystals.

[0039] (3) The prepared seed solution is filtered to remove coarse and fine seed particles, thereby obtaining seed particles with uniform particle size. Adding these seed particles to titanium solution for hydrolysis results in a hydrolyzed slurry with a more suitable particle size, more uniform particle size distribution, lower viscosity, and higher washing efficiency. This is because if the particle size is uneven, the aggregation of large and small particles is more severe, leading to higher slurry viscosity. This fundamentally solves the problem of high viscosity and low washing efficiency in metatitanic acid. With lower hydrolyzed slurry viscosity, the filtration time is shorter, and the shorter washing time can reduce the iron content of the filter cake to the production requirements. Salt-treated slurry has lower viscosity, resulting in more uniform mixing. The salt-treated agent coats the TiO2 particles more densely, and the calcined product particles are closer to spherical. Spherical particles scatter light more strongly, resulting in higher covering power.

[0040] (4) The removal of fine-grained seed crystals prevents over-burning of excessively fine particles during the calcination of metatitanic acid. This avoids the influence of sintered particles on the covering power.

[0041] (5) The loose silicon coated with TiO2 has a honeycomb structure. After coating, it has a high hiding power. Attached Figure Description

[0042] Figure 1 The particle size is that of the hydrolyzed metatitanic acid obtained in Example 1 of this invention.

[0043] Figure 2 The particle size is that of the hydrolyzed metatitanic acid obtained in Example 2 of this invention.

[0044] Figure 3 The particle size is that of the hydrolyzed metatitanic acid obtained in Example 3 of this invention.

[0045] Figure 4 The particle size is that of the hydrolyzed metatitanic acid prepared in Comparative Example 1 of this invention.

[0046] Figure 5 The particle size is that of the hydrolyzed metatitanic acid obtained in Comparative Example 2 of this invention.

[0047] Figure 6 The particle size is that of the hydrolyzed metatitanic acid obtained in Comparative Example 3 of this invention.

[0048] Figure 7 It is the particle size of the titanium dioxide product obtained in Example 1 of the present invention.

[0049] Figure 8 It is the particle size of the titanium dioxide product obtained in Example 2 of the present invention.

[0050] Figure 9 It is the particle size of the titanium dioxide product obtained in Example 3 of the present invention.

[0051] Figure 10It is the particle size of the titanium dioxide product obtained in Comparative Example 1 of this invention.

[0052] Figure 11 It is the particle size of the titanium dioxide product obtained in Comparative Example 2 of this invention.

[0053] Figure 12 It is the particle size of the titanium dioxide product obtained in Comparative Example 3 of this invention.

[0054] The blue line represents the cumulative distribution of particle size, while the red line represents the interval distribution of particle size. Detailed Implementation

[0055] The present invention will be described in detail below with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of the present invention can be combined with each other.

[0056] Example 1 1. Seed preparation: Titanium liquid parameters: TiO2: 200g / L, F value: 1.95, Fe / TiO2: 0.28, stability 500mL.

[0057] (1) Take 200 mL of titanium oxysulfate solution and put it into a 1000 mL glass beaker. Turn on the stirrer and add 200 mL of deionized water to adjust the concentration of titanium oxysulfate solution to 100 g / L. Heat the solution to 45 °C. At the same time, take a 60 g / L NaOH solution into a glass beaker and preheat it to 30 °C.

[0058] Add 60 g / L NaOH solution using an axial flow pump at a time of 39 minutes and 18 seconds, controlling the final pH value to 4.0. Heat to 60°C and allow to mature for 30 minutes. Cool to 25°C with ice water before use.

[0059] Table 1. NaOH solution addition time in Example 1 (2) The prepared seed crystals are filtered in batches through a two-stage filtration process to remove coarse and fine particles, and the resulting seed crystals with uniform particle size are adjusted to pH 4.0.

[0060] (3) Add seed crystals to titanium liquid for hydrolysis, first washing, bleaching, second washing, salt treatment, calcination to prepare crude rutile titanium dioxide, roller milling, and wet milling.

[0061] (4) Coating: Prepare a titanium dioxide slurry with a concentration of 500 g / L by wet milling. Heat the slurry to 45°C and add sodium silicate with a weight percentage concentration of 20% (calculated as SiO2) and 4.0% for 20 minutes. Pump 5% sulfuric acid into the axial flow pump, controlling the flow rate, for 40 minutes, and control the pH value to 5.0. Let it mature for another 10 minutes. Add aluminum sulfate (calculated as Al2O3) and sodium hydroxide solution with a weight percentage concentration of 10% and 5% in parallel flow. The amount of aluminum sulfate added is 2.0%, the pH value is controlled at 10 in parallel flow, the addition time is 40 minutes, and the maturation time is 10 minutes. Wash with water, dry, and steam powder.

[0062] Example 2 Seed preparation: Titanium liquid parameters: TiO2 200 g / L, F value: 2.05, Fe / TiO2: 0.2, stability 500 mL.

[0063] (1) Take 200 mL of titanium oxysulfate solution and put it into a 1000 mL glass beaker. Turn on the stirrer and add 300 mL of deionized water to adjust the concentration of titanium oxysulfate solution to 80 g / L. Heat the solution to 55 °C. At the same time, take 80 g / L NaOH solution into the glass beaker and preheat it to 40 °C.

[0064] Add 80 g / L NaOH solution using an axial flow pump over a period of 33 minutes and 33 seconds. Maintain a final pH of 3.5. Heat to 60°C and allow to mature for 10 minutes. Cool to 25°C with ice water before use.

[0065] Table 2. NaOH solution addition time in Example 2 (2) The prepared seed crystals are filtered in batches through a two-stage filtration process to remove coarse and fine particles, and the resulting seed crystals with uniform particle size are adjusted to pH 4.0.

[0066] (3) Add seed crystals to titanium liquid for hydrolysis, first washing, bleaching, second washing, salt treatment, calcination to prepare crude rutile titanium dioxide, roller milling, and wet milling.

[0067] (4) Coating: Prepare a 400 g / L titanium dioxide slurry from the wet-milled titanium dioxide, heat it to 60°C, and add 5.0% sodium silicate (20% by weight, calculated as SiO2) for 40 minutes. Pump in 5% sulfuric acid using an axial flow pump, controlling the flow rate, for 50 minutes, and control the pH value at 6.5. Let it mature for another 20 minutes. Add 10% aluminum sulfate (calculated as Al2O3) and 5% sodium hydroxide solution in parallel flow, with the amount of aluminum sulfate added being 3.0%. Control the pH value in parallel flow at 8.0, add it for 30 minutes, and mature for 15 minutes. Wash with water, dry, and steam.

[0068] Example 3 Seed crystal preparation: Titanium liquid specifications: TiO2: 200 g / L, F value: 2.0, Fe / TiO2: 0.25, stability 500 mL.

[0069] (1) Take 200 mL of titanium oxysulfate solution and put it into a 1000 mL glass beaker. Turn on the stirrer, add 244.4 mL of deionized water to adjust the concentration of titanium oxysulfate solution to 90 g / L, and heat it to 50 °C. At the same time, take a 60 g / L NaOH solution into a glass beaker and preheat it to 35 °C.

[0070] Add 70 g / L NaOH solution using an axial flow pump at a time of 34 minutes and 53 seconds. Control the final pH value to 3.8. Heat to 60°C and allow to mature for 20 minutes. Cool to 25°C with ice water before use.

[0071] Table 3. NaOH solution addition time in Example 3 (2) The prepared seed crystals are filtered in batches through a two-stage filtration process to remove coarse and fine particles, and the resulting seed crystals with uniform particle size are adjusted to pH 4.0.

[0072] (3) Add seed crystals to titanium liquid for hydrolysis, first washing, bleaching, second washing, salt treatment, calcination to prepare crude rutile titanium dioxide, roller milling, and wet milling.

[0073] (4) Coating: Prepare a titanium dioxide slurry with a concentration of 300 g / L by wet milling. Heat the slurry to 50°C and add sodium silicate with a weight percentage concentration of 20% (calculated as SiO2) and 4.5% (calculated as SiO2) for 30 minutes. Pump in 5% sulfuric acid using an axial flow pump, controlling the flow rate, for 60 minutes, and control the pH value to 6.0. Let it mature for another 15 minutes. Add aluminum sulfate (calculated as Al2O3) and sodium hydroxide solution with a weight percentage concentration of 10% and 5% (calculated as Al2O3) in parallel flow. The amount of aluminum sulfate added is 2.5%, the pH value is controlled at 9.0, the addition time is 35 minutes, and the maturation time is 15 minutes. Wash with water, dry, and steam powder.

[0074] Comparative Example 1 Seed crystal preparation: Titanium liquid parameters: TiO2: 200 g / L, F value: 1.95, Fe / TiO2: 0.28, stability 500 mL.

[0075] conventional seed crystal preparation methods (1) Measure 50 mL of sodium hydroxide with a concentration of 100 g / L into a beaker. According to the requirements for seed preparation with a titanium-alkali ratio of 6.4:1, measure 162 mL of titanium liquid with a TiO2 concentration of 198 g / L. Heat the titanium liquid and alkali to 80 °C respectively. Pour the titanium liquid into the alkali beaker after about 3 minutes to obtain orthotitanic acid crystal nuclei. Take 10 mL of seed crystals and test its initial stability of 165 mL. Continue to heat to 95 °C for aging. After 6 minutes, test the stability of the seed crystals of 110 mL. (2) Add seed crystals to titanium liquid for hydrolysis, first washing, bleaching, second washing, salt treatment, calcination to prepare crude rutile titanium dioxide, roller milling, and wet milling.

[0076] (3) Coating: Prepare a titanium dioxide slurry with a concentration of 400 g / L by wet milling. Heat the slurry to 50°C and add sodium silicate with a weight percentage concentration of 20% (calculated as SiO2) and 4.5% (calculated as SiO2) for 30 minutes. Pump in 5% sulfuric acid using an axial flow pump, controlling the flow rate, until the pH value is 6.0, adding for 35 minutes. Let it mature for another 15 minutes. Add aluminum sulfate (calculated as Al2O3) and sodium hydroxide solution with a weight percentage concentration of 10% and 5% (calculated as Al2O3) in parallel flow. The amount of aluminum sulfate added is 2.5%. Control the pH value in parallel flow to 9.0, add for 30 minutes, and mature for 15 minutes. Wash with water, dry, and steam powder.

[0077] Comparative Example 2 In the second step of Example 1, (2) is changed to: the prepared seed crystals are passed through a Buchner funnel to remove coarse particles, and the resulting seed crystals with the coarse particle size removed are obtained.

[0078] Comparative Example 3 The second step (2) of the same example 1 is changed to: (2) the prepared seed crystal is filtered with a ceramic membrane to remove fine particles, and the fine particles are removed.

[0079] In Examples 1-3, the prepared hydrolyzed seed crystals were treated to remove both coarse and fine-sized seed crystals. The resulting seed crystals had a uniform particle size distribution and moderate size. The hydrolyzed metatitanic acid particles had a narrow and uniform particle size distribution and a small aspect ratio. Consequently, the final titanium dioxide product had uniform particle size, strong light scattering ability, and high hiding power.

[0080] Titanium dioxide hiding power test method: After titanium dioxide is prepared into a slurry, it is coated onto a transparent polyester film. After the coating is dried, the whiteness value of the coating on a black board and a white board is measured by a whiteness meter. The ratio of black board to white board is used to characterize the hiding power of the coating.

[0081] Take 300 mL of hydrolyzed slurry and filter and wash it with water using a Buchner funnel with a diameter of 11 cm.

[0082] Table 4. Washing time and iron content of hydrolyzed metatitanic acid prepared in Examples 1-3 and Comparative Examples Adding uniformly sized seed crystals to titanium liquid for hydrolysis results in a hydrolyzed slurry with a more suitable particle size, more uniform particle size distribution, lower viscosity, higher washing efficiency, shorter washing time, and lower iron content.

[0083] Table 5. Covering power of titanium dioxide prepared in Examples 1-3 and Comparative Examples and a certain foreign sample. In the embodiment, the seed crystals in step 2 remove coarse and fine particles, thereby obtaining seed crystals with uniform particle size. Since the seed crystals are uniform in size, the hydrolyzed metatitanic acid particles are also uniform in size, resulting in good filtration performance of the hydrolyzed metatitanic acid.

[0084] The hydrolyzed seed crystals prepared in Comparative Example 1 were untreated, resulting in uneven seed crystal size and inconsistent hydrolyzed metatitanic acid particle size. The wide particle size distribution and tight bonding between coarse and fine particles led to fewer pores in the filter cake and fewer water flow channels, requiring a longer washing time to remove iron-based impurities. Furthermore, fine-particle-size seed crystals resulted in finer hydrolyzed metatitanic acid particles that were prone to sintering after calcination, reducing light scattering ability and thus the hiding power of titanium dioxide. Conversely, coarser seed crystals produced coarser hydrolyzed metatitanic acid particles and coarser titanium dioxide particles, further reducing light scattering ability and ultimately lowering the hiding power of the finished titanium dioxide product.

[0085] Comparative Example 2 showed that after removing coarse particles from the seed crystals, there were more fine-sized seed crystals, resulting in a higher proportion of finer hydrolyzed metatitanic acid particles. The prolonged washing time for hydrolyzed metatitanic acid caused the ferrous ions to easily oxidize to ferric ions, which readily form Fe(OH)3 precipitate. This precipitate cannot be removed by washing and instead increases the iron content in the hydrolyzed metatitanic acid. After treatment, the finer particles from the hydrolyzed metatitanic acid were more prone to sintering upon calcination, requiring significant energy to break up the aggregated particles. Furthermore, the increased number of finer particles resulted in a higher proportion of fine particles in the finished titanium dioxide product, which reduces the hiding power of the final product.

[0086] In Comparative Example 3, the seed crystals prepared to remove fine particles had a coarse particle size, resulting in coarse hydrolyzed metatitanic acid particles. The water flow rate was too fast, and the washing time for the hydrolyzed metatitanic acid was too short. This made it difficult to completely remove iron from the hydrolyzed metatitanic acid, and the iron content in the washed metatitanic acid was actually higher. The coarse particle size of the hydrolyzed metatitanic acid also resulted in a coarse particle size in the calcined sample, and these excessively coarse particles reduced the product's opacity.

[0087] The above embodiments should be understood as being used only to illustrate the present invention more clearly, and not to limit the scope of the present invention. After reading the present invention, any modifications of the present embodiments by those skilled in the art will fall within the scope defined by the appended claims.

Claims

1. A method for preparing high-opacity titanium dioxide, characterized in that... Includes the following steps: S1. Take a titanium oxysulfate solution with a concentration of 80-100 g / L (based on TiO2), an F value of 1.95-2.05, and an Fe / TiO2 ratio of 0.2-0.

28. Heat the titanium oxysulfate solution to 40-55°C, preheat the alkali solution to 30-40°C, add the preheated alkali solution to the heated titanium oxysulfate solution, and add the preheated alkali solution for 30-40 minutes. Control the final pH value to 3.0-4.0, then raise the temperature to 60°C for aging for 10-30 minutes, and then cool to below 25°C to obtain a seed crystal solution. S2. Filter the seed solution obtained in S1 to remove seed crystals with a particle size greater than 0.35 μm; S3. Filter the seed solution after S2 again to remove seed crystals with a particle size of less than 0.16μm, and obtain the filtered seed solution. S4. Add the filtered seed solution prepared in S3 to the titanium liquid, and then perform hydrolysis, first washing, bleaching, second washing, salt treatment, calcination, preparation of rutile titanium dioxide powder, roller milling, and wet milling to obtain wet-milled titanium dioxide slurry. S5. Coat, mature, wash, dry, and air-powder the wet-milled titanium dioxide slurry from S4 to obtain the final product.

2. The method for preparing high-opacity titanium dioxide according to claim 1, characterized in that, In S1, the alkaline solution is added to the titanium oxysulfate solution, and the pH reaches 2.0 in 18-20 minutes.

3. The method for preparing high-opacity titanium dioxide according to claim 2, characterized in that, In S1, the alkaline solution is added to the titanium oxysulfate solution. The time for the pH to reach 2.5 from 2.0 is 5-8 minutes, the time for the pH to reach 3.0 from 2.5 is 3-6 minutes, the time for the pH to reach 3.5 from 3.0 is 2-5 minutes, and the time for the pH to reach 4.0 from 3.5 is 1-3 minutes.

4. The method for preparing high-opacity titanium dioxide according to claim 1, characterized in that, In S1, the alkaline solution is added to the titanium oxysulfate solution, and the final pH value is controlled at 3.5-4.

0.

5. The method for preparing high-opacity titanium dioxide according to claim 1, characterized in that, The concentration of the alkaline solution in S1 is 60-80 g / L.

6. The method for preparing high-opacity titanium dioxide according to any one of claims 1-5, characterized in that, In S2, a Buchner funnel with filter cloth is used to filter out coarse seed crystals.

7. The method for preparing high-opacity titanium dioxide according to any one of claims 1-5, characterized in that, In S3, a ceramic membrane filter is used to remove fine particles of seed crystals, and the filtration is carried out by a water circulation pump.

8. The method for preparing high-opacity titanium dioxide according to any one of claims 1-5, characterized in that, The coating process in S5 specifically includes the following steps: Prepare a wet-milled titanium dioxide slurry to a concentration of 300-500 g / L, heat to 45-60℃, add sodium silicate with a mass concentration of 4-5% over 20-40 minutes, add an acidifier with a mass concentration of 5-10% until the pH of the slurry reaches 5.0-6.5 over 40-60 minutes, allow to mature for 10-20 minutes, add an aluminum sulfate solution with a mass concentration of 2-10%, and then add a dilute alkali solution with a mass concentration of 5-10% to control the pH of the slurry to 8-10 over 30-40 minutes.

9. The method for preparing high-opacity titanium dioxide according to claim 8, characterized in that, After adding dilute alkali solution to S5, the maturation time is 10-15 minutes.

Citation Information

Patent Citations

  • Production method of titanium dioxide particles

    CN103880070B

  • Preparation method of titanium dioxide with high covering power for laminated paper

    CN106395893A